The influence of brand image, brand awareness, and brand trust on Samsung smartphone purchase decisions (study on Samsung smartphone consumers at Sinar Mas seluller shop Semarang city) - Putri Tiara Indah Sari; Rokh Eddy Prabowo (Jurnal Ekonomi, 2024)
The purpose of this study is to partially analyze the influence of  brand image, brand awareness, and brand trust  on purchasing decisions. The population in this study is  Samsung smartphone buyers  at Sinar Mas Seluller Shop Semarang City. The sample size was 96 respondents selected using purposive sampling techniques. Primary data was collected using questionnaires, while secondary data used library techniques. Based on the results of the SPSS version 24 test, the results were obtained that the research instrument test showed all valid indicators and all reliable variables. Based on the F test, all independent variables simultaneously influence the purchase decision. Based on the results of the regression coefficient and t-test, it shows that  the brand image variable has a positive and significant influence on the purchase decision, the brand awareness  variable has a positive and significant effect on the purchase decision, and the brand trust variable has a positive and significant effect on  the purchase decision.